Pengaruh Komitmen Organisasional, Locus of Control, dan Posisi Auditor terhadap Penerimaan Perilaku Disfungsional Audit - Triono, Hermawan (Jurnal Ilmiah Aset, 2020)
This study aims to analyze whether the organizational commitment, locus of control, and auditor’s position affect the acceptance of dysfunctional audit behavior.The population of this study are 100 independent auditors who work at Public Accountant Office on Semarang. Meanwhile, the sample of this research are 80 auditors. The Data were collected through questionnaire and analyzed using path analysis technique. The result indicates that there is positive influence of locus of control on acceptance of dysfuctional audit behavior, negative influence of auditor’s position on acceptance of dysfunctional audit behavior, and negative influence of organizational commitment on acceptance of dysfunctional audit behavior.